Betraying trust and the elusive nature of ethnicity in Burundi - Turner, Simon ; 0000-0002-5521-8141 (Traitors : Suspicion, Intimacy, and The Ethics of State-Building, 2010)
In the African Great Lakes region, Hutu and Tutsi for the most part live peacefully side by side, while at times they have committed genocide and other atrocities in the name of ethnicity. On the one hand, ethnicity is strong enough to mobilize hundreds of thousands of ordinary Hutu peasants in Rwanda to kill, maim, and molest their Tutsi neighbors and to have the Tutsi-dominated army in Burundi systematically and brutally kill more that 100 000 Hutu civilians. On the other hand, they have so much in common that it is strongly debated and heavily disputed whether one can in fact talk of ethnic groups in these two, small central African states. Much of the literature on the area claims that the conflicts are not about ethnicity at all: that ethnicity is constructed, instrumentalized, and manipulated by political elites in order to achieve certain goals and that the main issue is access to resources and/or political power. Others claim that the conflicts are less about the skillful manipulation of identities by greedy elites and more about genuine grievances among the common population.1 Neither position explains in full, however, the ambiguity of ethnicity in the region-the fact that enemies become friends and friends become enemies almost overnight. In this chapter, I explore the ambiguous nature of ethnicity through the figure of the traitor. The traitor transgresses the boundaries of ethnic belonging, thereby permitting the constant negotiation and policing of these boundaries. However, if we go beyond this obvious observation, we find that there are several kinds of traitors at play and that each kind of traitor figure presents a different kind of sociality. The first kind of traitor in popular imagination is the Hutu next door who used to interact freely with Tutsi and who suddenly turns into a dangerous ethnic "Other," killing Tutsi neighbors and friends indiscriminately. He may also be the schoolmate whose ethnic identity you did not know, basically because it did not matter, until you discover not only that he is Tutsi but that he has known your ethnicity all along and has been hatching secret plans against you. They are perceived as traitors in the sense that they break the faith and trust of their close friends and neighbors, betraying intimate relations (kin, friends, neighbors) due to a loyalty toward ethnic categories. In these constructions of the traitor in popular discourse, the traitor is believed to be created by an inner, demonic, and very real ethnic identity, and betrayal lies in pretending that ethnicity does not matter. There is a second kind of ethnic traitor, however, in Burundian narratives on ethnicity: people who choose to turn their backs on their "true" ethnic identity. This is especially a central narrative among the Hutu, who are concerned with Hutu individuals who try to become Tutsi for reasons of personal gain. By marrying Tutsi women or accepting high positions in the Tutsi government or army, they are believed to be seeking personal advantages by turning their backs on their true ethnic identity. These stories of betrayal build on another notion of sociality, one that is based on ethnic loyalty. Based on concrete case studies of the various perceptions of treachery in Burundian ethnopolitics, this chapter explores how these two apparently opposing modes of treachery relate to the ambiguous position of ethnicity, thereby contributing to ethnic violence in Burundi. While the first type of treason destroys interethnic harmony and the second type blurs ethnic belonging, both kinds reveal an understanding of ethnicity as inescapable yet malleable. The traitor, on the one hand, illustrates the ability of individuals to manipulate and hide ethnic identities, while, on the other hand, the narratives point out that individuals cannot escape their inherent and deep-seated ethnic identities in the long run.